Transport of nanoparticles in porous media and its effects on the co-existing pollutants. (15th August 2021) - Ling, Xin; Yan, Zhenhua; Liu, Yuxuan; Lu, Guanghua
Abstract: Nanomaterials are widely used in daily life owing to their superior characteristics. The release and transport of nanoparticles (NPs) in the environment is inevitable during their entire life cycle, posing a risk to the aquatic environment. Thus, considerable attention has been focused on the fate and behavior of NPs in porous media, as well as the co-transport of NPs with other pollutants. In this review, current knowledge about the retention and transport behavior of NPs in porous media is summarized. NP transport in porous media is dominated by various internal and external factors, including the characteristics of NPs, porous media, and water flow. Generally, NPs with high density, small particle size, and surface coating are easily transported in porous media with the characteristics of large size, smooth surface, and low water saturation. Meanwhile, high pH and velocity, low temperature, and natural organic matter-containing fluids are also conducive to NP transport. Aggregation, adsorption, straining, and blocking are the primary mechanisms by which NPs affect the transport of co-existing pollutants in porous media. Current research on NP transport has been performed predominantly using modal porous media (e.g., sand and glass beads); however, there is a large gap between simulated and natural porous media. Further studies should focus on the transport, fate, and interaction of NPs and coexistent pollutants in natural porous media, as well as the coupling mechanisms under actual environmental conditions. Graphical abstract: Image 1 Highlights: The transport of NPs is affected by the properties of NPs, porous media and fluid. Aggregation, adsorption, straining and blocking are the main mechanisms involved. NPs can change the diffusion of co-existing pollutants and co-transport with them. Interaction of NPs and pollutants in natural media requires further investigation.